The Antarctic Circumpolar Current as a dispersive agent in the Southern Ocean: evidence from bivalves - Güller, Marina; Puccinelli, Eleonora; Zelaya, Diego Gabriel (Marine Biology)
Over the past decades, several studies have revealed that the traditional view of the Antarctic Circumpolar Current (ACC) as an agent for species dispersal in the Southern Ocean is not applicable to all taxa. Some species are actually circum-Antarctically or circum-sub-Antarctically distributed, but some other species actually comprise species’ complexes, with cryptic taxa occurring at different areas. However, to date, few of the invertebrate species formerly reported as widespread in the Southern Ocean have been re-analyzed using genetic techniques. This study examined whether two geographically distant areas of the sub-Antarctic region under the influence of the ACC, the Southern tip of South America (SSA) and the Prince Edward Islands (PEI), share some marine invertebrate species. For that, members of two genera of bivalves, Gaimardia and Hiatella, were selected. As part of this study, we found extremely low genetic differentiation between specimens from SSA and PEI. In addition, shared haplotypes were found between these two areas. Our results confirm that Gaimardia trapesina and one same species of Hiatella (“Hiatella O”) are present in both areas. Given that these two species are found on macroalgae, natural rafts appear as the most plausible means of dispersal of juveniles and adults, although in the case of Hiatella O, additional larval dispersion cannot be discarded. In any of these cases, dispersion should be facilitated (or even determined) by the ACC. Thus, this study provides new evidence in favour of considering the ACC as an effective dispersive agent in the Southern Ocean. Fil: Güller, Marina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Puccinelli, Eleonora. University of Cape Town; Sudáfrica Fil: Zelaya, Diego Gabriel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y ...